PENERAPAN PENGENDALIAN DAN MANAJEMEN RISIKO PADA AKTIVITAS PENJUALAN TANAH KAVLING DI PERUSAHAAN PENGEMBANG KAWASAN INDUSTRI PT X - , Fajarudin; , Dr. Hardo Basuki,M.Soc.Sc., ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Risk is a problem that certainly will be the factors that may hinder the realization of organizational goals or, worse, that risk can thwart the realization of the ideals of the organization as a whole. Risk is something which intrinsically has a negative impact on targets and company strategy, therefore, necessary to risk management. Risk management is the process of measuring or assessing risk and developing strategies for managing it. Strategies that can be taken include the transfer of risk to another party, avoiding risk, reducing the negative effects of risk, and accommodate some or all of the consequences of certain risks. Integrated risk management is a process whereby the various risks are identified, measured, and controlled throughout the organization. Through integrated risk management, any strategic decisions taken are always based on valid and reliable information. Thus the decision was expected to be able to effectively anticipate events in the future and reduce uncertainty. In various articles, Enterprise Risk Management (ERM) sometimes appears in other terms such as "strategic risk management", "integrated risk management", or "holistic risk management". All these terms refer to the same concept is that everything is looked at risk and risk management in a comprehensive, no longer with the traditional approach where risk is managed separately and differently in an organization.